Różnice kursowe w świetle prawa bilansowego i podatkowego - Krzeszowski, Wojciech Dawid (Foreign Exchange Rate Variations in the Light of the Balance Sheet and Fiscal Law, 2006)
Foreign exchange currency transactions are a specific group of business operations of an enterprise. They are related to the occurrence of foreign exchange rate variations. In some cases, recording such transactions in the books of an enterprise can pose a problem. The following article presents selected comments on the issue.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (4); 2006; nr 1119, s. 159-168